NU dan Paradigma Teologi Politik Pembebasan: Refleksi Historis Pasca Khittah - Muhammad Masyhuri (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
This research means to study the religious institution’s role to liberate from the problems of ummah in their real life. Theological study on dimension of liberation here aims to investigate what are Muslim scholars’ opinions on this issue and how to implement their thought on political reality. This study employs historical description focuses on historical dynamic of Nahdlatul Ulama (NU) political position and its institution, especially after returning to the khittah of 1926. This study also analyzes those dynamics in relation to liberation theology. This study shows that institutional dynamic of NU in politic and its reflection, be it is in accommodatif  respond or opposition, related to its stands between religion and the state is strongly inspired from Sunni political paradigm. However, there have been some variation related to sociological politic in implementing this Sunni paradigm in reality. Institutionally, the implementation to reflect liberation theology can be identified as substantialistic, realistic and rationalistic. The root of liberation on theology in NU can be seen from its emphasis on the issues of peace, pluralism, humanity and justice. By implementing this liberation of theology, there are some changes in the dynamic of NU history in the forms of growing number of educational institution, strengthening religious’ roles and positions, increasing community participation in social, economic and politic without confounding with institutional religious politisation.